Multi-instrumental observation of mesoscale tropospheric systems in July 2021 with a potential impact on ionospheric variability in midlatitudes - Koucká Knížová, Petra; Potužníková, Kateřina; Podolská, Kateřina; Hannawald, Patrick; Mošna, Zbyšek; Kouba, Daniel; Chum, Jaroslav; Wüst, Sabine; Bittner, Michael; Kerum, Jacek (Frontiers in Astronomy and Space Sciences, 2023)
The ionosphere as a part of the Earth's atmosphere supports wide range oscillations. Within them acoustic-gravity waves (AGW) form an important part. AGWs distribute energy and momentum from the source region over large distances. Significant portion of AGWs originates in the lower atmosphere and propagates through the atmosphere up to the ionospheric heights where, due to the coupling between neutral and ionized particles, it could be detected as wave-like disturbances of the plasma. Primarily the ionosphere behavior is driven by solar and geomagnetic activity while the influence from neutral and below laying regions of the atmosphere most of the time forms substantially smaller part of the observed variability. However, it could significantly alter ionospheric behavior. Our study is limited to a time span of rather low solar and geomagnetic activity in order to highlight neutral atmosphere influence. In the study we focus on two tropospheric situations above Europe that may lead to AGW generation that propagate up to the F layer where they potentially induce variability that we observe within ionospheric plasma parameters.